PENERAPAN SANKSI PENGHENTIAN KEGIATAN KEPADA PELAKU USAHA DALAM PERKARA PERSEKONGKOLAN TENDER PADA KOMISI PENGAWAS PERSAINGAN USAHA - Dewi, Inamawati Mastuti; Anggoro, Teddy (PALAR (Pakuan Law review), 2023)
AbstractBusiness competition law enforcement in Indonesia is carried out by the Business Competition Supervisory Commission  through roles including supervision, consultation and investigation. One example of activities that are prohibited in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition is conspiracy. Conspiracies that are rife in government procurement of goods/services or government tenders. Business Competition Supervisory Commission can impose sanctions in the form of orders to Business Actors to stop activities on the issue of tender conspiracy, but in practice these sanctions are supplemented by a ban on participating in government tenders originating from Central Government Expenditure Budget /Local Government Expenditure Budget. Thus there is a difference between regulation and application related to sanctions in the conspiracy tender. Keywords: Business Competition Supervisory Commission, Conspiracy, Tender, Sanctions. AbstrakPenegakan hukum persaingan usaha di Indonesia dilaksanakan oleh Komisi Pengawas Persaingan Usaha (KPPU) melalui peran antara lain pengawasan, konsultasi, maupun penyelidikan. Salah satu contoh kegiatan yang dilarang dalam Undang-Undang 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat adalah kegiatan persekongkolan. Persekongkolan yang marak terjadi dalam pengadaan barang/jasa pemerintah atau tender pemerintah. KPPU dapat menjatuhkan sanksi berupa perintah kepada Pelaku Usaha untuk melakukan penghentian kegiatan pada perkara persekongkolan tender dimaksud, namun pada praktiknya sanksi tersebut ditambah dengan larangan mengikuti kegiatan tender pemerintah yang bersumber dari APBN/APBD. Dengan demikian terdapat perbedaan antara pengaturan dan penerapan terkait sanksi dalam persekongkolan tender. Kata Kunci: KPPU, Persekongkolan, Tender, Sanksi.